17-Allylamino-17-demethoxygeldanamycin induces downregulation of critical Hsp90 protein clients and results in cell cycle arrest and apoptosis of human urinary bladder cancer cells - Karkoulis, Panagiotis K (BioMed Central, 2010)
BACKGROUND: 17-Allylamino-17-demethoxygeldanamycin (17-AAG), a benzoquinone ansamycin antibiotic, specifically targets heat shock protein 90 (Hsp90) and interferes with its function as a molecular chaperone that maintains the structural and functional integrity of various protein clients involved in cellular signaling. In this study, we have investigated the effect of 17-AAG on the regulation of Hsp90-dependent signaling pathways directly implicated in cell cycle progression, survival and motility of human urinary bladder cancer cell lines. METHODS: We have used MTT-based assays, FACS analysis, Western blotting, semi-quantitative RT-PCR, immunocytochemistry and scratch-wound assay in RT4, RT112 and T24 human urinary bladder cancer cell lines. RESULTS: We have demonstrated that, upon 17-AAG treatment, bladder cancer cells are arrested in the G1 phase of the cell cycle and eventually undergo apoptotic cell death in a dose-dependent manner. Furthermore, 17-AAG administration was shown to induce a pronounced downregulation of multiple Hsp90 protein clients and other downstream effectors, such as IGF-IR, Akt, IKK-α, IKK-β, FOXO1, ERK1/2 and c-Met, resulting in sequestration-mediated inactivation of NF-κB, reduced cell proliferation and decline of cell motility. CONCLUSIONS: In total, we have clearly evinced a dose-dependent and cell type-specific effect of 17-AAG on cell cycle progression, survival and motility of human bladder cancer cells, due to downregulation of multiple Hsp90 clients and subsequent disruption of signaling integrity.